PENGARUH LAMA PENYIMPANAN DAN WARNA KERABANG TERHADAP KUALITAS INTERNAL TELUR AYAM RAS - Rangga Saputra; Dian Septinova; Tintin Kurtini (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
The eggs susceptible to damage and loss of quality due to the entry of bacteria into the egg so that can’t function properly. In addition to the storage duration, eggshell colour factors also affect the level of people's preference for chicken eggs. The darker egg shell colour the thicker the shell and less the pores so the evaporation will be less. Egg shell colour is relatively dark and has a thicker shell and smaller pores that evaporation of the lower egg. The research was to know the effect of storage duration and colour of eggs shell towards the internal eggs quality (egg weight, Haugh Units, and yolk colour); the best effect of storage duration and colour of egg shell towards the internal eggs quality. This study was carried out on March 12 – April 2, 2014 was at the Laboratory Animal Production and Reproduction, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The method was completely randomized design with a nested pattern, factor storage time (7 days and 14 days) as the main plot and eggshell colour intensity factor (light brown and dark brown) as the subplot. Each treatment was repeated 5 times and its experimental unit consist of 3 eggs. The parameters measured were egg weight, yolk colour, and Haugh Units (HU). Data was analyzed with analysis of variance. If there is a real variable Duncan test at 5% significance level.The results was the treatment had significant effect (P <0.05) to the HU value, but not significant (P> 0.05) to egg weight and yolk colour. The storage duration 7 days and eggshell dark brown gived the best of HU.